Factor affecting employee engagement / Nuralia Atiqah Misrun - Misrun, Nuralia Atiqah (Faculty of Business and Management, 2019)
Employees who are properly engaged and managed can be considered as esteemed asset and they can become competitive advantages to the organization as people are difficult to imitate (Anitha, 2014). The researcher find that there is the need to conduct the research on factors that contribute employees engagement particularly in companies at Malaysia. The research objective is to determine the relationship between compensation, leadership, and training and development with employee engagement. The target respondents in this research are employees who work at Headquarters Syarikat Air Melaka Berhad Jalan Hang Tuah, Melaka. The research covered a sample 132 employees from 200 employees. Primary data are used in this research through the development of questionnaires. The collected data will be analyzed using Statistical Packages for Social Science (SPSS) software. Descriptive analysis, Frequency analysis, Pearson Correlation analysis, Multiple Regression analysis and Reliability Test analysis. The result of this research will be useful to the organization and allowed the organization to be able to implement policy, remuneration or plan in retain their talented employee.